Educação á Distância e Universidade Aberta do Brasil: Quando a Mercantilização do Ensino e a Precarização da Docência Alcançam um Novo Ápice - Silva, Solonildo Almeida da (2011)
Taking as reference onto-methodological the Marxist critique of the capitalist system, we will explain the current moment of capitalism, from the contributions of Istuãn Mészáros about what he calls sociometabolic system of the capital. At the structural crisis of this system the production is characterized as destructive being growing the context of the precariousness of the work. As palliative measures focused on the crisis management, the capital, under the representation of the State, has been delegating to the education the social function of formation for citizenship which in its mark should contribute to the materialization of democratic relations and of development in the molds of the current society. We deal with the meszarian thesis that education in the scenario of the capital structural crisis becomes a necessary mechanism for the administration of this crisis situation. In these terms, we analyze the restructuring of production and labor, as well as the market condition that the education has taken on this new order of capital. In the contextualization of the educational market, we elucidate the problematic of the mercantilization of the distance teaching in the face of New Technologies of Information and Communication and before the process of precariousness of the teaching work. We discuss the consolidation process of Distance Education (DE), worldwide, to then turn it to the Brazilian sphere. First, we present the main events that marked the historical development of DE in the world, since the records of discontinuous and fragmented experiences as the pioneers institutional systematizations developed to the stage where it is. We present the history of DE in Brazil, which is characterized by laws and public policies that define their trends in recent years, and the main models adopted in the country. We display statistical data that express the growth of DE modality in recent years, and the vast project of international organizations in support of education for all, in which the distance education appears as the main motto of this goal. We analyze the insertion of higher education in the field of distance teaching modality with data released by federal government in the process of expansion of DE that has been regimented by Aberta University. Taking the Marxian perspective, we examine in this sense, the function that DE acquired as a goal of democratization of higher education, whose objectives focus on fulfillment of the education program for all that links this condition to the formation for the citizenship and the employability of force labor to the market. We emphasize that higher education has become a very profitable commodity in the promising market of education. We treat the main characteristics of teachers/tutors that give class personally and teachers/tutors that give class virtually in Ceará, analyzing four chosen institutions (UFC, IFCE, UECE and FDR) in which we focus on the criterion of performing throughout the state of Ceará and the publications of public announcements for selective processes in hiring teachers/tutors for each of these institutions. We visited the analysis of studies elaborated in relation to the precariousness of the teachers and its implication impact on the performance of teaching duties now performed by non-teachers, but teachers/tutors